심전도 및 심장초음파 피검사자 대상 심장질환 빈도분석: 건강보험심사평가원 2차자료 중심으로 - 오혜정(Hye-Jeong Oh), 성열훈(Youl-Hun Seoung) (Journal of Radiological Science and Technology, 48(3), 2025)
This study analyzed the frequency of heart diseases among individuals who underwent electrocardiography (ECG) and echocardiography, using data from the Health Insurance Review and Assessment Service (HIRA). The analysis was conducted based on healthcare claims data from 2019 to 2022, and heart disease-related data were extracted from four key HIRA tables (T200, T300, T400, and T530). Frequency analysis was performed using SAS Enterprise Guide to examine the prevalence of heart diseases diagnosed through ECG and echocardiography, differences between patients who underwent a single test and those who received multiple tests and patterns by medical specialty, age, sex and type of medical institution. The results showed that hypertensive heart disease accounted for 93.58% of all cases making it the most frequent diagnosis and also had the highest rate of repeated testing. In contrast conditions such as angina and atrial fibrillation had relatively lower rates of repeated testing. By medical specialty internal medicine accounted for the highest proportion of heart disease diagnoses (81.8%), while emergency medicine primarily diagnosed acute heart conditions. Additionally age-specific analysis revealed that 76.86% of heart disease cases occurred in individuals aged 60 and above and 93.69% of diagnoses were made at primary care institutions. 본 연구는 건강보험심사평가원(HIRA)의 데이터를 활용하여 심전도 및 심장초음파 검사를 받은 피검사자를 중심으로 심장질환 발생 빈도를 분석하였다. 2019~2022년 HIRA 요양급여비용 청구자료를 바탕으로 진행되었으며, HIRA의 4개 주요 테이블 (T200, T300, T400, T530)에서 심장질환 관련 데이터를 추출하였다. SAS Enterprise Guide를 활용하여 빈도분석을 수행하였으며, 심전도 및 심장초음파 검사를 통해 진단된 심장질환의 빈도, 1회 검사와 2회 이상 반복 검사 간 차이, 진료과별 심장질환 유형 및 연령·성별·의료기관 유형별 분석하였다. 그 결과, 고혈압성 심장질환이 전체 데이터의 93.58%를 차지하며 가장 높은 빈도를 보였으며, 반복 검사 비율도 가장 높았다. 협심증, 심방세동 등의 질환은 반복 검사 빈도가 상대적으로 낮았다. 진료과별 분석에서는 내과에서 심장질환 진단 비율이 81.8%로 가장 높았으며, 응급의학과에서는 급성 심장질환 진단이 주로 이루어졌다. 또한, 연령별 분석에서 60세 이상에서 심장질환 발생률이 76.86%를 차지하였으며, 1차 의료기관에서 93.69%의 진단이 이루어지는 것으로 나타났다.